The Role of Catecholamins in the Regulation of Children's Body Hemodynamic - V. Shaykhelislamova, Maria; B. Dikopolskaya, Natalia; A. Bilalova, Gulfia; Yu. Fomina , Maria; L. Zefirov, Timur (International Journal of Psychosocial Rehabilitation, 2020)
The catecholamine system stands out among other hormonal systems by its participation in the regulation of hemodynamic functions. In children, the level of hormones and mediators is not constant, which explains the lack of formation of the mechanisms of regulation of the circulatory system. Long-term static postural stress of the child at school and home causes rapid muscle fatigue and mental stress, which does not exclude vegetative dysfunctions and abnormalities in the cardiovascular system (CVS). Conducted a comprehensive study of the state of hemo dynamics and adrenal glands in children 7 years old, an analysis of the correlations between their parameters. Daily and portioned urine was collected in spring and autumn, and the levels of adrenaline (A), norepinephrine (NA), dopamine (DA) and DOPA were recorded by fluorometry. The state of the circulatory system was studied by indicators of cardiac output - stroke volume of blood (CLC) and minute circulation - IOC. Thoracic rheoplethysmography with an analog-to-digital converter was used. Peripheral circulation was recorded by analysis of blood pressure (systolic, diastolic and mean hemodynamic blood pressure (SBP), (DBP) and (SRS). The method of pair correlation was used to study the interdependence of indicators of the endocrine system and the circulatory system. The relationship of the hormones of the adrenal medulla and the parameters of the CVS of the child's body is shown. This was most clearly manifested in the state of the functional stress of the body, a variant of which was the dosed static load. A relationship was found between the hemodynamic reaction and the level of excretion of catecholamines (CA) and DOPA in the post-isometric period. Isometric muscle tension of the upper limb causes an increase in the tone of peripheral vessels and a parallel increase in NA in children of 7 years of age. At the same time, at the end of the school year, there is a negative dynamics in the excretion of A, NA, and DA, accompanied by a decrease in the CRF and IOC in the recovery period. A decrease in the activity of adrenergic influences on the pumping function of the heart is indicated by a break in the correlation bonds of A and NA with UOK and IOC. Thus, the study allowed us to identify the relationship between hemodynamic parameters and the level of catecholamine excretion in the post-isometric period in children 7 years old. The effect of NA on the state of peripheral vascular tone has been proven, unidirectional changes in the level of NA excretion and DBP values, total peripheral vascular resistance (OPSS) after static muscular effort have been established.